From Ukraine to Hungary: A Specific Case of Student Mobility - Sütő, Zsuzsanna (Central European Journal of Educational Research, 2025)
Bibliography of the reviewed book: Pallay, K. (2024). Mobility, career development, integration. Mobility, career development, integration. Students of the Balassi Institute in Transcarpathia]. University of Debrecen Centre for Higher Education Research and Development (CHERD).